Chomatin mass from previously aggregated, pyknotic, and fragmented monolayer nuclei is a source for dome cell nuclei generated by amitosis: Differentiation of Ishikawa Domes, Part 3 - Fleming,Honoree (PeerJ PrePrints, 2016)
Ishikawa endometrial epithelial cells are capable of differentiation from monolayer cells into fluid-enclosing hemispheres through a surprisingly complex series of structural changes as discussed in this and in two accompanying papers (Fleming, 2016a; Fleming 2016b). The process starts with the dissolution of cell membranes in defined regions throughout a monolayer that has been stimulated to differentiate (Fleming, 1995). Aggregated nuclei become wrapped in membranes containing mitochondrial carboxylases, and apparently generated by contiguous mitochondria. These mitonucleons are involved in vacuole formation that elevates the syncytium into a predome (Fleming, 2015a). The mitonucleons begin to fall apart several hours after formation as the enveloping membranes are breached and the pyknotic chromatin undergoes profound changes (Fleming, 2015b). Chromatin deconstruction, with attendant disappearance of the typical ovoid nuclear structure, results in chromatin fibers that fill the envelope formed by the apical and basal membranes of the syncytium, now stretching over a cavity filling with fluid. In the next several hours, hematoxylin staining, greatly diminished when nuclei were fragmented, reappears in an irregular mass of chromatin out of which nuclei form amitotically and increase in numbers until they fill the envelope. Subsequently cell membranes form around the nuclei. Domes can enlarge and even extend into tubules by becoming vacuolized and undergoing the same amitotic process that created the dome initially.
Keywords: amitosis; chromatin mass; emerging nuclei; envelope limited chromatin; copy number variants; genomic mosaicism; mitonucleon generated amitosis